IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN AL-QUR’AN PADA ANAK USIA DINI - Annida, Alya; Yarliani, Ikta; Pratiwi, Hardiyanti (Titik Fokus Karya, 2023)
Early Quranic education is essential, and therefore, an appropriate method is needed to teach it. One of the methods used is the Ummi Method. This research employs a qualitative approach with a case study type. The research subjects are the ustadz, ustadzah, and students at Rumah Qur'an Baiturrahmah Unit 0003 Teluk Tiram. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the implementation of the Ummi Method covers three main aspects: planning, implementation, and evaluation. Planning includes teacher and prospective teacher training, Ummi certification, and internship programs for prospective teachers. The implementation consists of seven stages: opening, apperception, concept introduction, concept understanding, skills development, evaluation, and closing. Additionally, other Islamic educational teachings, such as daily prayers, fiqh materials, short hadiths, and Asma Ul-Husna, are introduced to children. The evaluation is divided into three categories: daily evaluation, book level progression evaluation, and end-of-semester evaluation. The result achieved is an improvement in the ability of early childhood students to read the Quran. Factors supporting the planning of the Ummi Method in Quranic education include teacher and prospective teacher training, Ummi certification, established learning procedures, and clear time management. Factors supporting the implementation of the Ummi Method include an easily followed rhythm for the children. In terms of evaluation, the support factor is the clear progress report. The only obstacle found is in the implementation phase, which is the lack of adequate space, as one group must study in the terrace.